Les neurosciences de l’éducation sont- elles capables de rendre les pratiques enseignantes plus efficaces ? - Samia Ilhem NOUADRI (Université de M'sila, 2020)
This study aimed at cognitive didactics which mainly focuses on modern cognitive research. The rapid development of neuroscience in recent decades has brought applications that are both possible and relevant to the world of education. Indeed, while brain science deals with the processes on which learning is based, education aims to apply it in concrete life, in particular in pedagogical life. However, although the bridges are clear between these two systems, neuroscience is still evolving in the world of education. So, it is important to work on attention, to what extent educational neurosciences effective and contributory are in the learning process, can they support learners to learn better?
Keywords: (Attention, neuroscience, education, Didactics, cognitive, brain.)